Technology Heterogeneity and Poverty Traps: A Latent Class Approach to Technology Gap Drivers of Chronic Poverty. Issue 2 (1st February 2023) - Hill, Daniel; McWhinnie, Stephanie F.; Kumar, Shalander; Gregg, Daniel
Abstract: The analysis of household wealth dynamic remains an important methodology in the identification of poverty traps. To overcome measurement issues in survey data, livelihoods-based approaches of the dynamics of poverty are typically examined using panel regressions of a livelihoods regression on household assets and other socio-economic factors over time. In this paper, we characterise the livelihoods regression as a 'livelihoods technology', and use a latent class-technology approach to account for heterogeneity in how households generate a livelihood. We use a detailed dataset from rural India covering 213 households across 2001–2014, and control for selection issues through a Heckman Selection model. Our results are the first in the wealth dynamics literature to show that substantial heterogeneity exists in the technologies with which households generate their livelihoods. Importantly, we show that accounting for heterogeneity in household livelihoods 'technologies' more readily identifies different equilibria in wealth levels and provides previously foregone information on who is poor and why they remain poor.